Rapid Diagnosis of Bacterial Pneumonia in Under-five Children by Latex Particle Agglutination Test in Urine (Bangladesh Journal of Medical Microbiology, 2016)
Streptococcus pneumoniae and Haemophilus influenzae type b are the main causes of community-acquired bacterial pneumonia in developing countries including Bangladesh. This study was carried out to find a rapid diagnostic method for early detection of bacterial pneumonia. Latex Particle Agglutination Test (LPAT) was done in urine for quick detection of capsular antigens of S. pneumoniae and H. influenzae type b. Three hundred children were enrolled based on clinical criteria as defined by the WHO. Among them, 70 pneumonic children, who had total white blood cell counts around  20000/ mm3, Neutrophils ? 75% and consolidation on chest X-rays, were selected for LPAT in urine. Some 20 children of the same age group, who had chest diseases other than pneumonia, were selected as sick control group. Among 70 pneumonic cases, 36 (51.43%) were positive by LPAT in urine. Out of 36 LPAT-positive cases, 19 (52.7%) were positive for S. pneumoniae and 17 (47.3%) were positive for H. influenzae type b by specific anti-sera. The LPAT is thus appears as a quick and reliable test for the diagnosis of bacterial pneumonia cases caused by S. pneumoniae and H. influenzae type b.Bangladesh J Med Microbiol 2007; 01 (01):17-20